2003
DOI: 10.1159/000069510
|View full text |Cite
|
Sign up to set email alerts
|

Promoter Usage and Estrogen Regulation of Prolactin Receptor Gene in the Brain of the Female Rat

Abstract: Mechanisms underlying hormonal regulation of prolactin receptor (PRL-R) gene in the brain are unknown. The 5’-untranslated region of PRL-R mRNA in peripheral tissues contains at least three alternative first exons (1A, B, C) that are expressed as tissue-specific, suggesting the differential usage of PRL-R gene promoters. The present study aimed to investigate: (1) the possible regulation of PRL-R mRNA levels by estrogen in in vitro and in vivo tissues; (2) which exon (1A, or 1B, or 1C)-containing PRL-R mRNA tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 33 publications
2
22
3
Order By: Relevance
“…These results indicate that PRL upregulates the expression of mE1 4 -Prlr mRNA in the murine choroid plexus and that the increased expression of mE1 3 -and mE1 5 -Prlr mRNAs at lactation may depend on factors other than PRL. It has been previously shown that estrogen upregulates Prlr gene expression in the choroid plexus (Pi et al 2003) as well as Prl gene expression in the pituitary gland (Shull & Gorski 1990, Kansra et al 2005. Our experiments in this study involving the ovariectomized mice showed that estrogen upregulates the expression of mE1 4 -Prlr mRNAs in the Prl C/K mice but not in the Prl K/K mice.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…These results indicate that PRL upregulates the expression of mE1 4 -Prlr mRNA in the murine choroid plexus and that the increased expression of mE1 3 -and mE1 5 -Prlr mRNAs at lactation may depend on factors other than PRL. It has been previously shown that estrogen upregulates Prlr gene expression in the choroid plexus (Pi et al 2003) as well as Prl gene expression in the pituitary gland (Shull & Gorski 1990, Kansra et al 2005. Our experiments in this study involving the ovariectomized mice showed that estrogen upregulates the expression of mE1 4 -Prlr mRNAs in the Prl C/K mice but not in the Prl K/K mice.…”
Section: Discussionsupporting
confidence: 48%
“…In addition, it has been reported that PRL enhances its own uptake in the choroid plexus (Mangurian et al 1992). Supporting this function, a high level of PRLR expression in the choroid plexus has been observed during lactation when the plasma PRL level is also high (Muccioli & Di Carlo 1994, Escalada et al 1996, Sugiyama et al 1996, Pi & Grattan 1999, Augustine et al 2003, Pi et al 2003, Nogami et al 2007, Anderson et al 2008. Also, PRLR expression in this brain region increases during the stress response, accompanying an increase in the plasma PRL level (Fujikawa et al 1995).…”
Section: Introductionmentioning
confidence: 82%
“…the long-form PrLr is known to be involved in most of the PrL functions mediated by the Jak2/stat5 (janus kinase 2/signal transducer and activator of transduction 5) intracellular signaling pathway [5,10,14], whereas the function and intracellular signaling system of the short-form PrLr is poorly understood. in the rat choroid plexus, the expression of the long-and short-form PRLR mrNas has been observed [3,4,15,27,30]. the molecular mechanisms of transcriptional activation of the E1 4 first exon, and the transport system of PrL mediated by long-or short-form PrLr in the choroid plexus remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…PrL is known to be transported from the blood to the cerebrospinal fluid (CSF) via a PrLr-mediated system in the choroid plexus [37], and PrL enhances its own uptake in the choroid plexus [21]. Many studies have reported an increase in PRLR mrNa levels in the choroid plexus during lactation that correlate with plasma PrL level increases [1,2,13,24,27,30,31,33]. These findings suggest that regulation of PRLR expression in the choroid plexus is critical for PrL action in the brain.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated that the higher levels of PRL-R mRNA in the rat brain in late pregnancy and the following lactating period are dependent on the expression of E1 4 , Tanaka et al 2002. It has also been shown that the expression levels of PRL-R mRNA in the different brain regions are regulated by oestrogen, which increases the utilization of E1 2 and E1 3 first exons (Pi et al 2003). In the liver, the expression of the PRL-R gene is known to be regulated by sex steroid hormones; up-regulation by oestrogen and down-regulation by testosterone (Jolicoeur et al 1989, Sakaguchi et al 1994.…”
Section: Introductionmentioning
confidence: 96%